An Examination of Differences in the New Bone Formation Promoted by Different Doses of Recombinant Human Parathyroid Hormone during Mandibular Distraction Osteogenesis. Issue 2 (February 2016) - Tang, Zheng-Long; Bai, Shuo; Zhu, Peng-Na; Li, Yong-Di; Wang, Dong-Xiang; Cai, Yang
Abstract : Background: The administration of different doses of parathyroid hormone to promote mandibular distraction osteogenesis remains unclear. The objective of the present study was to examine the effects of recombinant human parathyroid hormone on new bone formation during mandibular distraction osteogenesis and to investigate the dose-effect relationship associated with this phenomenon. Methods: A total of 45 rabbits were used to establish the mandibular distraction osteogenesis model. The rabbits were divided into a control group (that received a subcutaneous injection of 1 ml of saline every other day) and experimental groups A, B, C, and D (that received subcutaneous injections of 10, 20, 30, and 40 μg/kg of recombinant human parathyroid hormone, respectively, every other day). On days 1, 7, and 14 of the consolidation period after the distraction had been completed, new bone in the distraction region was examined through histomorphometric investigation and bone mineral density testing. Results: On days 1, 7, and 14 of the fixation period, the number of osteoblasts, trabecular bone area, and bone mineral density were greater in each experimental group than in the control group. On day 1 of the consolidation period, group C featured the highest average number of osteoblasts. On day 14 of the consolidation period, group C exhibited the highest bone mineral densities and largest trabecular bone areas. Conclusions: Intermittent subcutaneous injections of recombinant human parathyroid hormone can promote new bone formation during mandibular distraction osteogenesis. Different doses of recombinant human parathyroid hormone promoted mandibular distraction osteogenesis to differing extents.